Baseline MD Anderson Symptom Inventory Score is Strongly Associated With Patient-reported Acute and Late Toxicity Following (Chemo) Radiotherapy for Head and Neck Cancers. Issue 10 (October 2022) - Barker, C.L.; Price, G.J.; Lee, L.W.; McPartlin, A.
Abstract: Aims: Patient-reported outcomes measures (PROMs) are an increasingly recognised end point of radiotherapy studies. We hypothesised that the baseline PROMs score is the strongest predictor for acute and late scores after treatment. We assessed the strength of association of baseline MD Anderson Symptom Inventory (MDASI) scores, alongside other known factors for patient- or clinician-reported toxicity, with acute (6-week) and late (12-month) scores in head and neck cancer (HNC) patients following (chemo)radiotherapy. Materials and methods: This was a retrospective analysis of longitudinal MDASI scores for 247 patients receiving (chemo)radiotherapy for HNC via multivariable linear regression. The factors investigated were: baseline symptom score, age, sex, concurrent chemotherapy, disease stage, radiotherapy fractionation, prior definitive surgery and performance status. Patients with a baseline score >4 in any item were defined as symptomatic in that category. Results: Patients rated symptomatic for an MDASI item pre-treatment on average reported statistically ( P < 0.0005) and clinically (>–1.5) significant reductions in scores 6 weeks and 12 months after (chemo)radiotherapy for all considered sub-items except taste, dryness of mouth and problems with teeth. Conversely patients asymptomatic at baseline reported a worsening of scores at both time points. Other investigated factors showed little association with changes in MDASI scores following treatment. Conclusions: Our data show that baseline MDASI scores are strongly associated with patient-reported toxicity 6 weeks and 12 months after (chemo)radiotherapy for HNC. Patients who are symptomatic at baseline can experience an early and durable benefit from treatment. This finding can inform discussions with patients before therapy and has implications for use of PROMs scores for the assessment of toxicity in randomised trials. Highlights: Predictive factors for MDASI evolution after (chemo)radiotherapy for head and ceck cancer assessed. Baseline MDASI score the only factor associated with score evolution up to 1 year post-therapy. Symptomatic patients experience an early and durable benefit to symptoms from treatment. Finding has implications use of patient-reported outcome measures as end points of clinical trials.